2016
DOI: 10.1007/s13280-015-0752-7
|View full text |Cite
|
Sign up to set email alerts
|

Managing Swedish forestry’s impact on mercury in fish: Defining the impact and mitigation measures

Abstract: Inputs of anthropogenic mercury (Hg) to the environment have led to accumulation of Hg in terrestrial and aquatic ecosystems, contributing to fish Hg concentrations well above the European Union standards in large parts of Fennoscandia. Forestry operations have been reported to increase the concentrations and loads of Hg to surface waters by mobilizing Hg from the soil. This summary of available forestry effect studies reveals considerable variation in treatment effects on total Hg (THg) and methylmercury (MeH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 49 publications
1
46
1
Order By: Relevance
“…For example, decreased evapotranspiration can lead to an elevated water table, increased soil moisture, and ponding, all of which foster anoxic conditions favorable for methylation (Munthe and Hultberg 2004 ; Braaten and de Wit 2016 ; Kronberg et al 2016a ). Furthermore, fresh organic carbon inputs from logging debris left on the site may enhance microbial activity and MeHg production (Eklof et al 2016 ; Kronberg et al 2016a ). However, increased MeHg concentrations in streamwater draining harvested watersheds have only been clearly observed in some studies (Porvari et al 2003 ; Skyllberg et al 2009 ; Eklof et al 2012 ), whereas others have shown no significant change in MeHg response to forestry operations (Allan et al 2009 ; Eklof et al 2013 ; de Wit et al 2014 ; Kronberg et al 2016a ).…”
Section: Forestry and Deforestationmentioning
confidence: 99%
“…For example, decreased evapotranspiration can lead to an elevated water table, increased soil moisture, and ponding, all of which foster anoxic conditions favorable for methylation (Munthe and Hultberg 2004 ; Braaten and de Wit 2016 ; Kronberg et al 2016a ). Furthermore, fresh organic carbon inputs from logging debris left on the site may enhance microbial activity and MeHg production (Eklof et al 2016 ; Kronberg et al 2016a ). However, increased MeHg concentrations in streamwater draining harvested watersheds have only been clearly observed in some studies (Porvari et al 2003 ; Skyllberg et al 2009 ; Eklof et al 2012 ), whereas others have shown no significant change in MeHg response to forestry operations (Allan et al 2009 ; Eklof et al 2013 ; de Wit et al 2014 ; Kronberg et al 2016a ).…”
Section: Forestry and Deforestationmentioning
confidence: 99%
“…Off-road driving with heavy machines can cause wet soils to deform and displace resulting in deeper tracks and larger soil disturbance than on dry soils where shallower tracks are caused by compaction. Forestry conducted close to streams and lakes has been shown to increase the export of mercury (Eklöf et al 2016) and nutrients (Kreutzweiser et al 2008) to downstream environments (Kuglerová et al 2014). Soil damage in riparian zones can also lead to erosion from ruts and subsequent sediment deposition burying important spawning habitats (Kreutzweiser and Capell 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate stimulatory effects of forest harvest on MeHg formation and stream export, adjustment of forest management practices have been suggested, such as leaving zones of gallery forest along streams and avoiding soil disturbance and compaction by heavy machinery. 19,34 However, before such actions can be fully designed and implemented we need to better understand processes and factors in control of MeHg formation in forest soil (before and after harvest) and the spatial distribution of MeHg net producing "hot-spots" and their connections to…”
Section: Introductionmentioning
confidence: 99%